Tracy Crosswhite : A Steep Price - Book 6 - Dugoni, Robert (Thorndike, Maine : Center Point Large Print, 2018)
"Seattle homicide detective Tracy Crosswhite is plunged into a case of family secrets and murder when the body of a young woman who chose graduate school over an arranged marriage in India is found in an abandoned well"--
Keywords: Crosswhite, Tracy -- Fiction; Seattle (Wash.) -- Police Department -- Fiction; Cold cases (Criminal investigation) -- Fiction; Police -- Washington (State); Seattle; Fiction; Women detectives -- Fiction; Murder -- Investigation; Fiction; Missing persons -- Fiction; Detective and mystery fiction; Thrillers (Fiction)